2020
DOI: 10.1039/c9ra08199b
|View full text |Cite
|
Sign up to set email alerts
|

Effect of different pyrolysis temperatures on physico-chemical characteristics and lead(ii) removal of biochar derived from chicken manure

Abstract: Biochar derived from chicken manure, as an effective metal adsorbent, was prepared through a pyrolysis method at different pyrolytic temperatures (200, 400, 600, and 800 °C).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(8 citation statements)
references
References 38 publications
0
8
0
Order By: Relevance
“…The wideband observed at wavelength of 3200-3400 cm -1 is attributed to -OH from H 2 O, or phenolic groups (Chen et al, 2008;Melo et al, 2013). However, samples PPL350 and PPL450 did not show hydroxyl peaks in these regions; the loss of OH functionality is a consequence of reactions of decarbonylation, decarboxylation, and dehydration promoted with the increase of the pyrolysis temperature (Cuixia et al, 2020). The absorption in the region between 2920 and 2885 cm -1 (CH stretching) was attributed to aliphatic functional groups (Melo et al, 2013), and the increase in band intensity in the region of 1600 cm -1 showed the presence of ketones and conjugated quinones (C = O and C = C).…”
Section: Resultsmentioning
confidence: 93%
“…The wideband observed at wavelength of 3200-3400 cm -1 is attributed to -OH from H 2 O, or phenolic groups (Chen et al, 2008;Melo et al, 2013). However, samples PPL350 and PPL450 did not show hydroxyl peaks in these regions; the loss of OH functionality is a consequence of reactions of decarbonylation, decarboxylation, and dehydration promoted with the increase of the pyrolysis temperature (Cuixia et al, 2020). The absorption in the region between 2920 and 2885 cm -1 (CH stretching) was attributed to aliphatic functional groups (Melo et al, 2013), and the increase in band intensity in the region of 1600 cm -1 showed the presence of ketones and conjugated quinones (C = O and C = C).…”
Section: Resultsmentioning
confidence: 93%
“…In the infrared spectrum of BSM, the characteristics peaks at 1,071 cm -1 and 1,726 cm -1 are assigned to epoxide rings and carbonyl groups, respectively. The characteristic absorption peaks of hydroxyl (O-H) and amine (N-H) stretching vibrations appears at 3,482 cm -1 and 3,728 cm -1 [9,17,19]. In the spectrum of LEVO-loaded BSM, the above identified functional groups shifted or reduced.…”
Section: Biochar Supported Manganese Dioxide (Bsm) Composite Characterizationmentioning
confidence: 99%
“…In this research, authors explored the adsorption capacity of biochar derived from chicken feather waste. Chicken feather is regards as a waste material, emanates from food industry and its disposal often constitute nuisance to the environment [17][18][19].…”
Section: Introductionmentioning
confidence: 99%
“…Cuixia et al [139] carried out the pyrolysis of chicken manure at varying process temperatures from 200 to 800 °C and evaluated the use of chicken manure bio-char (CMB) for the removal of lead. The adsorption capacity of lead ions is positively correlated with process temperature and the maximum adsorption capacity of 242.57 mg/g was obtained using CMB prepared during pyrolysis of chicken manure at 800 °C.…”
Section: Pyrolysismentioning
confidence: 99%